Strengthening Sustainability in the Plastics Industry - IFC; World Bank (World Bank, Washington, DC, 2022)
Plastic is indispensable to modern life, so ubiquitous that it is virtually invisible. In many ways, it is an ideal material. Invented in the mid-19th century, plastic is remarkably versatile and relatively cheap to make, and it can be used as an inexpensive substitute for wood, glass, metal, and many other building and manufacturing materials. They play a vital role in driving industrial development, creating jobs, expanding opportunities, and generating wealth to improve people’s lives. But as the use of plastic has increased, so too have the environmental and social costs. The production process uses petrochemicals as a raw material and generates greenhouse gas emissions. Perhaps the biggest cost is the waste generated by discarded plastic goods. Most of the common plastics of today are not fully biodegradable, and that has created a cascade of environmental, financial, and health problems around the world. Every year, eight million tons of discarded plastics make their way into the oceans. With enhanced recycling systems and better cooperation among industry, governments, and consumers, these plastics can be readily collected, reused, and turned into something of value. In the past dozen years, the plastics industry has been urged to rethink the material’s entire lifecycle by developing manufacturing processes that use fewer natural resources, emit With support from the International Finance Corporation (IFC) and the private sector, the industry is embracing initiatives and investing in novel technologies that can reduce plastic’s environmental footprint and provide broad economic benefits while meeting the growing demand for products made of plastic.